2018
DOI: 10.1007/s00381-018-3867-x
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative paediatric cerebellar mutism syndrome: time to move beyond structural MRI

Abstract: PurposeTo determine the value of structural magnetic resonance imaging (MRI) in predicting post-operative paediatric cerebellar mutism syndrome (pCMS) in children undergoing surgical treatment for medulloblastoma.MethodsRetrospective cohort study design. Electronic/paper case note review of all children with medulloblastoma presenting to Great Ormond Street Hospital between 2003 and 2013. The diagnosis of pCMS was established through a scoring system incorporating mutism, ataxia, behavioural disturbance and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 44 publications
4
16
0
Order By: Relevance
“…Furthermore, compared to patients who did not develop PFS, those who experienced PFS had a consistent alteration in white matter integrity based on DTI of the bilateral SCP, as well as white matter changes in associated non-sensorimotor cortical areas (Morris et al, 2009). The involvement of the proximal dentatothalamocortical pathway due to damage to the SCP was replicated in a subsequent study using conventional MRI image processing [namely fluid-attenuated inversion recovery (FLAIR) and diffusion weighted imaging (DWI]) (Toescu et al, 2018b). This study also found changes in the dentate nucleus in patients with PFS, though this appeared to be a late onset pathology, rather than an acute problem tightly associated with behavioral morbidity (Toescu et al, 2018b).…”
Section: The Cerebellum In Human Affective and Cognitive Diseasesmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, compared to patients who did not develop PFS, those who experienced PFS had a consistent alteration in white matter integrity based on DTI of the bilateral SCP, as well as white matter changes in associated non-sensorimotor cortical areas (Morris et al, 2009). The involvement of the proximal dentatothalamocortical pathway due to damage to the SCP was replicated in a subsequent study using conventional MRI image processing [namely fluid-attenuated inversion recovery (FLAIR) and diffusion weighted imaging (DWI]) (Toescu et al, 2018b). This study also found changes in the dentate nucleus in patients with PFS, though this appeared to be a late onset pathology, rather than an acute problem tightly associated with behavioral morbidity (Toescu et al, 2018b).…”
Section: The Cerebellum In Human Affective and Cognitive Diseasesmentioning
confidence: 90%
“…Numerous studies have been undertaken to evaluate the changes in cerebellar structure and connectivity in patients who have experienced PFS (Morris et al, 2009; Patay et al, 2014; Avula et al, 2016; Toescu et al, 2018a, b). An evaluation of factors predisposing medulloblastoma patients to development of PFS found that tumor location proximal to the SCP made development of PFS more likely (Morris et al, 2009).…”
Section: The Cerebellum In Human Affective and Cognitive Diseasesmentioning
confidence: 99%
“…In recent years, magnetic resonance imaging (MRI) has been able to provide a [19,27,41,50], though a seminal paper in the field reported that more rostrally located fourth ventricle tumours had a significant statistical association with pCMS [18]. Early post-operative structural MRI showing oedema in middle or superior cerebellar peduncles is likely to be associated with pCMS [19,27], and generalised atrophy of the brainstem and cerebellar structures on delayed follow up MRI has been shown to be significantly more likely in pCMS [27].…”
Section: Structural Mrimentioning
confidence: 99%
“…The leading hypothesis for the occurrence of CM is mono-or bilateral disconnection of the efferent pathway from the cerebellum to the cortex, namely the cerebello-dentothalamo-cortical (CDTC) pathway [16]. This has been supported by a vast number of recent neuroimaging as well as lesion studies, showing that CM is associated with large [17], midline [18] tumours residing in proximity of the fourth ventricle and predicted by damage of the superior cerebellar peduncles, the dentate nucleus or the CDTC pathway itself [19]. Although tractography can improve preoperative surgical planning or predict postoperative deficit [19], its intraoperative reliability is limited by tissue displacement and brain-shift phenomena [20].…”
Section: Introductionmentioning
confidence: 93%